Lived Experiences of the Senior High School Learners at Goshen School of Technology and Humanities During the Covid 19 Pandemic - Taunan, Mikaela; Barcelona, Shailyn Rose Domingo; Sandoval, Rhyn-Niel Pines; Flaviano, Regie Loveras (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
COVID-19 had a strong impact on our economy, government, health care, and particularly on the education system. This study explored the lived experiences of Senior High School learners enrolled at Goshen School during the Covid-19 pandemic. The study applied Collaizzi’s Method in the data analysis and interpretations to identify meaningful information and organize it into themes. Themes that came out from the narratives of the participants were: They experienced issues on their learning modality, financial, technological, mental health, and lifestyle issues; Covid-19 Pandemic affects the personal, social, mental, and academic performances of the senior high school learners, and needed support system from family, peers, school, and community. The output of this study is a proposed model for senior high school learners during the Covid-19 Pandemic.